THE ROLE AND SIGNIFICANCE OF THE PORTRAIT GENRE IN AESTHETIC EDUCATION OF V-VIII CLASS STUDENTS OF GENERAL SECONDARY SCHOOLS (American Journal of Pedagogical and Educational Research, 2024)
In this article, the aesthetic education of schoolchildren by means of visual arts is justified from a scientific and theoretical point of view, the role of the portrait genre in providing the creative activity opportunities of all schoolchildren is revealed.